Device for the subsoil shield creation - D. G. Akhmedjonov (Сельскохозяйственные машины и технологии, 2017)
To make a subsoil membrane we designed a mounted plow device using an interpolymer complex (IPС) on the basis of carboxymethyl cellulose, urea formaldehyde and ortho-phosphoric acid. Spraying by IPC solution is possible due to a reservoir fixed on the tractor and nozzles on a tube 22-25 cm long and with a diameter of 15-20 mm. Parameters of tubes are determined by calculation. The IPC subsoil shield is made by designed device. So, when watering of a cotton on fields humidifying uniformity increases (faster water travel in a furrow), overflow water decreases (additional moistening at reduced water expense). Thus losses of water on deep filtering and evaporations from the lower soil layers decrease by 30-35 percent of the irrigating norm. As a part of the study we established the IPC composition promoting decrease in an infiltration, determined the location of nozzles on the llower side of moldboards providing protection against clogging by the soil. The optimum size of pressure when spraying by solution is 0.4-0.6 Pas.